2018
DOI: 10.1002/cplu.201800168
|View full text |Cite
|
Sign up to set email alerts
|

Boron Nitride for Hydrogen Storage

Abstract: Boron nitride, BN, for hydrogen storage emerged in the beginning of the millennium and there swiftly followed more than 15 years of efforts combining experimental laboratory works and to a greater extent computational predictions. BN has been considered mainly for the storage of molecular hydrogen, H2, by physisorption and/or chemisorption over a wide range of temperatures, that is, between −196 °C and 300 °C. Yet its potential has gone beyond the sorption of H2 as it has been also, although less extensively, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(27 citation statements)
references
References 97 publications
1
26
0
Order By: Relevance
“…Further chemical modifications of the BN surfaces would enhance their affinities of H 2 , [ 29 ] for example, substituting one B atom by one C atom in BNNTs, or one N atom with a O atom in BN nanosheets, leads to higher adsorption energy for the H 2 molecules. [ 30 ] Lei et al. experimentally found that ≈4 at% oxygen doping of BN nanosheets with the SSA of 536 m 2 g −1 had boosted the H 2 uptake to 5.7 wt% under 5 MPa at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Further chemical modifications of the BN surfaces would enhance their affinities of H 2 , [ 29 ] for example, substituting one B atom by one C atom in BNNTs, or one N atom with a O atom in BN nanosheets, leads to higher adsorption energy for the H 2 molecules. [ 30 ] Lei et al. experimentally found that ≈4 at% oxygen doping of BN nanosheets with the SSA of 536 m 2 g −1 had boosted the H 2 uptake to 5.7 wt% under 5 MPa at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings surely indicate the possibility of development of a viable dehydrogenation scheme from chemical hydrogen storage media with the application of acid initiators. [ 20 ]…”
Section: Resultsmentioning
confidence: 99%
“…These materials can be metallic structures that work like hydrogen sponges, [136][137][138] or they can be powders that release hydrogen upon contact with water or increased temperatures. [139][140][141][142] There has been a lot of research put into different solid materials for hydrogen storage, and it is not in the scope of this review to comment on all these methods, but we will select those that show promise for hydrogen storage in a maritime environment.…”
Section: Solid State Hydrogen Storagementioning
confidence: 99%